TRANSLATION TECHNIQUE OF TEMPLE`S TEXTS IN INDONESIA - Wening Sahayu; Sulis Triyono; Friyanto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to know the translation technique used by the translator in translating the word, phrase, even the sentence in Indonesian temple`s texts from Indonesian into English. This research employs descriptive qualitative method that is to describe the translation technique used. The data were taken from Indonesian temple`s text in Yogyakarta and the classification is based on the theory of translation technique. The result showed that from 281 data have been identified, there are 10 types of translation techniques applied from the results of the translation in the temple`s texts. The result showed that literal translation and borrowing are the most dominant techniques used. It happens because the translator focuses on source text oriented than the target text.